2014
DOI: 10.4236/fns.2014.510101
|View full text |Cite
|
Sign up to set email alerts
|

Finger Printing and Quantitative Analysis of <i>Cuscuta chinensis</i> Flavonoid Contents from Different Hosts by RP-HPLC

Abstract: Background: Cuscuta spp. known as dodders, have been used as traditional medicines in eastern and southern Asian countries for many disorders such as gastrointestinal, respiratory, endocrine, skin and neurological diseases (Drug of mania). Flavonoids are the main biologically active constituents in Cuscuta genus especially in C. chinensis. Our aim in this study was to identify and discriminate between C. chinensis samples which were collected from different hosts, by using the pattern recognition aided fingerp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Depending on the results of the preliminary laboratory studies, seed (L. albus) and vegetative growing stage (C. campestris) of the plants to be studied were determined. This choice is supported by the literature (Shekarchi et al, 2014;Hassan et al, 2019). The specimen identification was performed by Prof. Vagif Atamov from the Faculty of Science and Arts, Recep Tayyip Erdogan University in Rize, Turkey.…”
Section: Plant Materialsmentioning
confidence: 55%
See 1 more Smart Citation
“…Depending on the results of the preliminary laboratory studies, seed (L. albus) and vegetative growing stage (C. campestris) of the plants to be studied were determined. This choice is supported by the literature (Shekarchi et al, 2014;Hassan et al, 2019). The specimen identification was performed by Prof. Vagif Atamov from the Faculty of Science and Arts, Recep Tayyip Erdogan University in Rize, Turkey.…”
Section: Plant Materialsmentioning
confidence: 55%
“…have shown that phenolic and alkaloid contents of this plants are high. In addition, it has been observed that their potential to be natural alternative insecticides against many pests has been investigated (Thackray et al, 2000;Torres et al, 2009;Shekarchi et al, 2014;Selvi et al, 2017;Karamac et al, 2018;Hassan et al, 2019). However, no study has found effectiveness of the same plants against O. japonica.…”
Section: Introductionmentioning
confidence: 99%
“…Although the optimum harvest time of the C. songaricum stem at EFS has been demonstrated in previous studies [12,13], the mechanism of polysaccharide and flavonoid biosynthesis during growth stages is still limited. In this study, the maximum values of stem fresh weight, soluble sugar and total flavonoids contents, and antioxidant capacity in C. songaricum were observed at EFS compared with GS, VGS, and FS; a total of 367 DEGs co-expressed at the GS, VGS, and EFS with 109 genes directly involved in polysaccharide and flavonoid biosynthesis as well as growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…The types and contents of liposoluble components (e.g., β-sitosterol, hexadecanoic acid, and (Z)-9-octadecenoic acid) in C. songaricum were significantly different among different hosts [11]. For other parasitic plants, there were significant differences in contents of flavonoids (e.g., rutin, isorhamnetin, and kaempferol) in Cuscuta chinensis from different hosts [12]. Generally, the optimum harvest time of the C. songaricum stem is between the unearthed prophase (namely vegetative growth stage, VGS) and unearthed stage (namely early flowering stage, EFS), with greater contents of polysaccharides and protocatechuic acid compared with the flowering stage (FS) and fruiting stage [13,14].…”
Section: Introductionmentioning
confidence: 95%
“…Phytochemicals reported from the plant include 4-Hydroxy benzoic acid, paracoumaric acid, coumarin, vanillic acid, α-resorcylic acid, rutin, naringenin-7-rhamnoglucoside, marsileagenin A, 3-hydroxy triacontane-11-one, protocatechuic acid, caffeic acid, and ferulic acid. (Shekarchi et al, 2014) Keeping in view of its pharmacological properties, the authors have attempted to re-investigate the whole plant for its phytoconstituents and reported flavones salvigenin, chrisimaritin for the first time apart from the earlier reported quercetin and triterpenoid betulinic acid.…”
Section: Introductionmentioning
confidence: 99%